The English cult of literature: devoted readers, 1774 - 1880 - McKelvy, William R. (Victorian literature and culture series, 2007)
Orthodox narratives of literary sacralization -- Zealous protestants in literature: Lowth, Warton, and Percy -- Entertaining salvation: Scott's Jovial priests -- Common things hallowed: Keble and Macaulay -- Primitive traditions and modern readers: Gladstone's Homer -- Clerical fictions: Eliot's Scribal authority